Balancing Work Ethics and Non-Financial Compensation Enhancing Employee Productivity - Dudung Abdullah; Nita Hernita (Penerbit Goodwood, 2026)
Purpose: This study investigates the impact of work ethics and non-financial compensation on employee productivity at Perusahaan Umum Daerah Bank Perkreditan Rakyat (PERUMDA BPR) Majalengka, addressing the scarcity of empirical evidence regarding behavioral and non-monetary determinants influencing productivity in public-sector banking. Methodology/approach: A quantitative approach was used, with a survey conducted using questionnaires. The sample consisted of 50 employees, and the data were analyzed using multiple linear regression to determine the impact of work ethics and non-financial compensation on productivity. Results/findings: Both work ethics (? = 0.319; t = 2.258; p = 0.029) and non-financial compensation (? = 0.575; t = 2.515; p = 0.015) had positive and significant effects on employee productivity. The model accounted for 31% of the variance (R² = 0.310), and the overall regression was statistically significant (F = 10.534; p < 0.001). These findings demonstrate that both predictors significantly improved productivity. However, the substantial unexplained variance indicates the existence of additional organizational factors that were not addressed in this study. Conclusions: Improving non-monetary rewards and strengthening employees' work ethics can boost productivity, although these elements represent only part of a broader performance system.. Limitations: This study is limited to a single institution and self-reported data; future research should include additional variables and mixed-method approaches. Contributions: This study highlights the role of work ethics and non-financial compensation in boosting employee productivity in the banking sector, offering insights for organizations to improve performance through effective policies and rewards.